Staff experiences with implementing a case conferencing care model in nursing homes: a focus group study - Sigrid Nakrem; Geir-Tore Stensvik; Rickard Johan Skjong; Joan Ostaszkiewicz (BMC, 2019)
Abstract Background A majority of nursing home residents have dementia, and many develop neuropsychiatric symptoms. These symptoms are often caused by neuropathological changes in the brain, but modifiable factors related to quality of care also have an impact. A team-based approach to care that include comprehensive geriatric assessments to facilitate clinical decision-making and structured case conference meetings could improve quality of care and quality of life for the residents. Despite recommendations to adopt this approach, dementia care does not reach standards of evidence-based practice. Better implementation strategies are needed to improve care. A cluster randomised controlled trial with a 12-month intervention was conducted, and the experiences of staff from the intervention nursing homes were explored in a qualitative study after the trial was completed. The aim of the present study was to describe: (i) staff's experiences with the intervention consisting of comprehensive geriatric assessments of nursing home residents and case conferencing, and (ii) enablers and barriers to implementing and sustaining the intervention. Methods Four focus groups with a total of 19 healthcare staff were interviewed, representing four out of eight intervention nursing homes. Thematic content analysis was used to interpret the transcribed data. Results Two major themes emerged: 1) learning experiences and 2) enablers and barriers to implementation. The participants had experienced learning both on an organisational level: improvements in care and an organisation that could adjust and facilitate change; and on an individual level: becoming more conscious of residents' needs and acquiring skills in resident assessments. Participants described important enabling factors such as managerial support, drivers for change, and feasibility of the intervention for the local nursing home. Barriers to implementing and sustaining the intervention were time constraints, lack of staff training, unsuitable electronic patient record system for care planning and high complexities of care and instabilities that are present in nursing homes. Conclusions Quality improvements in nursing homes are difficult to sustain. In order to offer residents high quality of care that meet their individual needs, it is important for management and nursing home staff to be aware of and understand factors that enable or constrain change.